Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Explanation:-
★(i).
A = { 1,2}
⇛ n (A ) = 2
B = { 3,4,5,6}
⇛ n (B) = 4
n(A)+n(B) = 2+4 = 6
★(ii).
The symbol ⇛ means Implies
★(iii).
A = Phi = {}
B = phi = {}
AUB = { } U { } = { }
AUB = phi = { }
(iv).
AUB = BUA is called Commutative law in sets uner union .
★(v).
Null set = Void set = Empty set = { }
Number of elements in the empty set = 0
⇛ Cardinal number of null set is zero (0)
★(vi). If AUB = B then B is the super set and A is the sub set of B
★(vii). A = { 1,2,3,4}
B = {2,4,6,8}
A-B = {1,2,3,4} - { 2,4,6,8}
=> A-B = { 1,3}
★(viii). n(AUB) = 8
n(A) = 6
n(B) = 4
We know that
n(AnB) = n(A)+n(B)-n(AUB)
⇛ n(AnB) = 6+4-8
⇛n(AnB) = 10-8
⇛ n(AnB) = 2
or n(AUB)+n(AnB) = n(A)+n(B)
⇛ 8+ n(AnB) = 6+4
⇛ 8+ n(AnB) =10
⇛ n(AnB) = 10-8
⇛ n(AnB) = 2
Therefore, n(AnB) = 2
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.